Tributários de um grande reservatório neotropical: influência de variáveis ambientais e da paisagem no ictioplâncton e assembleia de peixes - Berger, Patricia Sarai da Silva (2019)
1. The large dams along the rivers have major impacts on fish communities, especially on large migratory species that have their migration routes blocked. When this occurs lateral tributaries may be an alternative for these species, since tributaries can enrich the diversity of fish in the main river, providing diverse environmental conditions, access to the spawning habitat, refuge for early stages of life, and promoting heterogeneity ecological, and so niche diversity. 2. Distribution patterns and the influence of the discharge in the ichthyoplankton were verified in tributaries of the Porto Primavera Reservoir, as well as the abundance and the structure of the fish assembly were analyzed and verified how they respond to the environmental variations and local landscape characteristics. For this purpose, we collected data from 2007 to 2010 and 2011 to 2018. 3. We verified that the discharge differed between tributaries and over the years, and this promote variations in the density of eggs and larvae of fish between tributaries and years, as well as the tributaries presented different larval species, including many long-distance migratory. In relation to the fish assemblage, the composition of fish species of the Aguapeí River was different from the other tributaries. The composition of the fish species of the Aguapeí River was different from the other tributaries, as well as this river presented the greatest abundance of fish, including long-distance migratory species, and possibly the different characteristics of the landscape and environmental variables contributed to this. 4. The tributaries of the Porto Primavera Reservoir (Aguapeí, Verde and Pardo) play a relevant role for fish species, since they function not only as spawning areas, but also as nursery and growth habitats, promoting wetlands and marginal lagoons with ideal conditions for species to complete their life cycle. Thus, these tributaries can mitigate the adverse influence of a large regulated river system.